Clinical study on the combined use of cardiovascular agents and statins in the treatment of coronary heart disease - Zhili Chen; Qianqian Zhang; Yue Zhang; Zhe Xu; Xiaozhe Yang (Pakistan Journal of Medical Sciences, 2026)
Objective: To evaluate the clinical efficacy of combining cardiovascular agents with statins in the treatment of coronary heart disease (CHD). Methodology: This was a retrospective study. A total of 110 patients diagnosed with CHD and treated at Shijiazhuang Eighth Hospital between January 2024 to December 2025 were enrolled and randomly divided into two groups, with 55 patients in each group. The control group received conventional therapy, including anticoagulation, coronary vasodilation, antiplatelet therapy, and treatments aimed at relieving myocardial ischemia. The treatment group received atorvastatin in addition to the conventional therapy administered to the control group. Clinical efficacy, lipid profiles, inflammatory markers, adverse reaction rates, and angina episodes were compared between the two groups following treatment. Results: The overall response rate was 95% in the treatment group and 80% in the control group, with a statistically significant difference (p = 0.02). Post-treatment levels of total cholesterol, triglycerides, and low-density lipoprotein cholesterol were significantly lower in the treatment group than in the control group, while high-density lipoprotein cholesterol levels were significantly higher (p = 0.00, respectively). Inflammatory markers, including interleukin-6, C-reactive protein, and tumor necrosis factor-alpha, were also significantly reduced in the treatment group compared with the control group (p = 0.00). Furthermore, the treatment group exhibited significantly fewer episodes of angina, with lower pain intensity and shorter duration than the control group (p = 0.00). The adverse reaction rate was 13% in the treatment group and 15% in the control group, showing no statistically significant difference (p = 0.76). Conclusion: The combination of cardiovascular agents with statins, particularly atorvastatin, demonstrates significant clinical benefits in the management of CHD. This regimen can effectively improve lipid metabolism, reduce systemic inflammation, and alleviate anginal symptoms, without increasing the risk of adverse events.